If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(-5 + -6x) = 4(3 + 5x) (-5 * -1 + -6x * -1) = 4(3 + 5x) (5 + 6x) = 4(3 + 5x) 5 + 6x = (3 * 4 + 5x * 4) 5 + 6x = (12 + 20x) Solving 5 + 6x = 12 + 20x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20x' to each side of the equation. 5 + 6x + -20x = 12 + 20x + -20x Combine like terms: 6x + -20x = -14x 5 + -14x = 12 + 20x + -20x Combine like terms: 20x + -20x = 0 5 + -14x = 12 + 0 5 + -14x = 12 Add '-5' to each side of the equation. 5 + -5 + -14x = 12 + -5 Combine like terms: 5 + -5 = 0 0 + -14x = 12 + -5 -14x = 12 + -5 Combine like terms: 12 + -5 = 7 -14x = 7 Divide each side by '-14'. x = -0.5 Simplifying x = -0.5
| -7x/5=49 | | -3+x/2=-6 | | 3/7=5/6+y | | 4z+4=2z+7 | | 2x+9=3y | | 8-1/3x=9 | | H+21=-51 | | X/9+12=9 | | 65+x-5+x=180 | | 42/1/2 | | t-7d=nt | | 8=9x-4 | | 1.6=80 | | 3(4x+3)=14x+5-2x+4 | | -2(3x+6)-4=3(x-1)-7x | | Fover-7-8=2 | | -2(3x+6)-4=3(x-1)-2x | | 3(4m+3)=3m-9 | | -2(3x+6)-4=3(x-1) | | -3+5b=-3 | | 5(1.084x+1)=8 | | -3+15=13x-2-12x | | 19*1/4 | | -5x-(6-3x)+15=-12 | | 16+-3a=22 | | 152x-190=19(8x-10) | | 0.2(a-16)=0.4a | | -5x-(6+3x)+15=-12 | | .25(9-2x)=0.125(3x+4) | | y=6-5x(-1) | | 3.5/6=x/9 | | -5x-(6x+3x)+15=-12 |